Rheumatoid meningitis: A rare cause of aseptic meningitis with frequently stroke-like episodes. Issue 5 (October 2018) - Schuster, Simon; Braass, Hanna; Iking-Konert, Christof; Schnoor, Ulrike; Matschke, Jakob; Gerloff, Christian; Thomalla, Götz; Magnus, Tim
Abstract : Background: Rheumatoid meningitis (RM) is a rare manifestation of rheumatoid arthritis (RA) and may present with stroke-like episodes. We describe diagnostic findings and the outcome in patients with RM. Methods: We identified 6 patients with RM in different stages of RA mostly admitted with stroke-like episodes or common features of meningitis. We used MRI, CSF, and histology for in-depth characterization. Results: We observed RM in 2 patients without history of RA, 1 patient with early seropositive RA, and 3 patients with late-stage RA. Recurrent stroke-like episodes occurred in 5 of 6 patients; headache and partial status epilepticus was in the foreground in 1 patient. Symptoms were accompanied by constitutional symptoms in all patients. MRI showed leptomeningeal or pachymeningeal fluid-attenuated inversion recovery hyperintensities with contrast enhancement. CSF mostly showed mild pleocytosis but can initially be normal. Anticitrullinated peptide antibodies (ACPA) and rheumatoid factor (RF) were positive in all patients. Histopathology revealed granulomatous inflammation in 2 patients. Response to steroids was prompt and further immunosuppressive treatment prevented recurrence. Conclusions: RM is a rare manifestation of RA and often presents with stroke-like episodes. It is currently not implemented in the workup of aseptic meningitis in national guidelines. Crucial clues for diagnosis included recurrent stroke-like episodes refractory to antiepileptic treatment, headache and constitutional symptoms, meningeal enhancement on MRI, CSF pleocytosis, and positive serology findings for ACPA and RF. Prognosis is favorable with early immunosuppressive treatment.